TEACHING VOCABULARY USING WORD SEARCH GAME WITH PICTURE - Wilda Trianti; Ikhsanudin Ikhsanudin; Eni Rosnija (Universitas Tanjungpura, 2019)
Abstract The aims of this research was to investigate the affect of teaching English vocabulary using word search game with picture to the seventh grade students of SMP Islam Haruniyah Pontianak in the school year of 2018/2019. The research was conducted to find out whether teaching vocabulary using word search game with picture effects the students` vocabulary achievement. This research was a pre-experimental study with one group pre-test and post-test design. The sample was the seventh grade students which consisted of 30 students. The data were collected using measurement technique. Then, the result of this research was analyzed using t-test. The data analysis showed that the t-ratio 10.91 and the t-critical was 2.045 based on t-table distribution using one tailed with α =0.025 which means that the t-ratio was higher than the t-critical. Therefore, the alternative hypothesis (Ha) which stated “Teaching vocabulary using word search game with picture to seventh grade students of SMP Islam Haruniyah Pontianak in the school year of 2018/2019 affects the students vocabulary achievement significantly” was accepted. It showed that word search game with picture affects significantly on the students’ English vocabulary achievement. Keywords: Word Search Game with Picture, Vocabulary, Affect.